Prevalence, Identification and Geographical Distribution of Eimeria spp. in Wild Rodents in Malang, East Java - Reza Yesica; Shelly Kusumarini; Ida Wisesa (IPB University, 2021)
Eimeria is a genus of apicomplexan parasites that infected various species and known as the enteric monoxenous coccidian. This study aims to determine the prevalence, identification and geographical distribution study of gastrointestinal protozoa Eimeria spp. in wild rodents in Malang city, East Java. A total of 74 rodents were collected from different part of Malang, using single live traps. Rats were euthanized with ketamine and xylazine. Samples of stools were taken from gastrointestinal tract. Coprological procedure using floatation method lead to the demonstration of Eimeria spp. oocysts in the faecal samples examined at 400 and 1000 magnifications of light microscope. Cultivation in dichromate potassium 2.5% was carried out for all of coccidian positive samples. The identification is based on morphology and morphometry. Eimeria identification data was analyzed descriptively, while the analysis of species and gender of rodents on prevalence used chi square. Result, the prevalence of Eimeria spp. in Malang is 11 (14.9%). It was suggesting coccidiosis caused by Eimeria nieschulzi. In addition, Chi square analysis showed that species of rats did not have a significant relationship (P>0.05) to the incidence of Eimeria infection, however it has significant correlation between gender of rats and Eimeria infection (P<0.05). The geographical of Eimeria spp. spots were showed in 8 Sampling area, in Lowokwaru, Klojen, Kedung kandang and Sukun sub district. Findings of this study showed that wild rodents in Malang city are infected with intestinal coccidian parasites.